Student’s Error in Solving Change and Relationship-PISA Problem and Its Scaffolding - Khusnah, Khotimatul; Ekawati, Rooselyna; Shodikin, Ali (Journal of Mathematical Pedagogy (JoMP), 2022)
Change and relationship problem is considered one of the most challenging PISA problems for students. This qualitative research aims to describe students' error in solving Change and Relationship-PISA problems in terms of self efficacy and the possible scaffolding. The subjects of this study were three students who had low, medium, and high self efficacy. The instrument used was a task-based interview in the form of Change and Relationship-PISA problems. The data were analyzed according to Newman’s Error Analysis and Scaffolding by Anghileri. The results of this study show that students with low self-efficacy experienced error in transformation, proccess skills, and encoding. Students with medium self-efficacy experienced error in proccess skills and encoding. Students with high self-efficacy only met error in encoding. To overcome these error, students with low self-efficacy are given scaffolding in the form of reviewing, explaining, and restructuring. While students with medium and high self-efficacy are given scaffolding in the form of reviewing and restructuring only. Errors made by students in the problem solving process vary for each level of self efficacy, so that the way to overcome with scaffolding also needs to be adjusted.